Mean posterior corneal power and astigmatism in normal versus keratoconic eyes. - Feizi, Sepehr; Delfazayebaher, Siamak; Javadi, Mohammad; Karimian, Farid; Ownagh, Vahid; Sadeghpour, Fatemeh (Journal of Ophthalmic & Vision Research)
Purpose: To compare mean posterior corneal power and astigmatism in normal versus keratoconus affected eyes and determine the optimal cut-off points to maximize sensitivity and specificity in discriminating keratoconus from normal corneas. Methods: A total of 204 normal eyes and 142 keratoconus affected eyes were enrolled in this prospective comparative study. Mean posterior corneal power and astigmatism were measured using a dual Scheimpflug camera. Correlation coefficients were calculated to assess the relationship between the magnitudes of keratometric and posterior corneal astigmatism in the study groups. Receiver operating characteristic curves were used to compare the sensitivity and specificity of the measured parameters and to identify the optimal cut-off points for discriminating keratoconus from normal corneas. Results: The mean posterior corneal power was −6.29 ± 0.20 D in the normal group and −7.77 ± 0.87 D in the keratoconus group (P < 0.001). The mean magnitudes of the posterior corneal astigmatisms were −0.32 ± 0.15 D and −0.94 ± 0.39 D in the normal and keratoconus groups, respectively (P < 0.001). Significant correlations were found between the magnitudes of keratometric and posterior corneal astigmatism in the normal (r=−0.76, P < 0.001) and keratoconus (r=−0.72, P < 0.001) groups. The mean posterior corneal power and astigmatism were highly reliable characteristics that distinguished keratoconus from normal corneas (area under the curve, 0.99 and 0.95, respectively). The optimal cut-off points of mean posterior corneal power and astigmatism were −6.70 D and −0.54 D, respectively. Conclusion: Mean posterior corneal power and astigmatism measured using a Galilei analyzer camera might have potential in diagnosing keratoconus. The cut-off points provided can be used for keratoconus screening.